A mechanical and pedagogical study of the pole vault - Mercado, R. (3rd European Pole Vault Conference - Köln 2008, 2008)
The goals of the pole vault project were: - Identify model technical parameters from coaches and scientists (Tidow, Groâ & Kunkel, Schade, et al., McGinnis, Linthorne) - Identify coaches` concepts of vital component parts and their interaction . Approach . Plant . Takeoff . Swing Review on a lot of surveys and studies on the subject.